Femoral cartilage thickness in patients with systemic sclerosis: It's relation to vitamin D - Gihan Omar; Rasha Ali Abdelmajeed; Amal Hassan; Yarah Aseem; Aliaa Hegazzy (Annals of Musculoskeletal Medicine - Peertechz Publications, 2018)
Background: Systemic sclerosis (SSc) is a chronic autoimmune progressive connective tissue disease characterized by widespread vascular, immune and fi brotic changes of the skin and internal organs. Articular cartilage thickness previously investigated in few. Lower levels of vitamin D have been demonstrated in SSc patients and may be related to more sever disease of longer duration and extensive skin involvement. Aim of this study was to compare the levels of vitamin D and femoral cartilage thickness (FCT) in SSc patients with that of controls and to analyze the associations between the (FCT), vitamin D levels and SSc-disease parameters. Material and Methods: Twenty five SSc patients diagnosed according to ACR/EULAR- 2013 classification criteria and twenty fi ve controls; apparently healthy age and sex matched were studied. Serum levels of 25-hydroxyvitamin D (25[OH] D) were assessed by (ELISA), levels less than ≤ 10ng/ mL are defi ned as defi ciency, while > 10 ng/mL is defi ned as insuffi ciency. The thickness of femoral articular cartilage was measured by ultrasonography (MSU) in patients and controls. Three midpoint measurements were taken from each knee: lateral femoral condyle (LFC), femoral intercondylar area (ICA) and medial femoral condyle (MFC). Result: We concluded that SSc patients seem to have thinner femoral cartilage values at all studied sites than that of control. A signifi cant difference was found in measurement of right inter condylar area (p=0.029), right medial condyles (p=0.022), left inter condylar area (p=0.036), left lateral condyle and left medial condyle (p=0.001) between patients and control. Lower levels of vitamin D was significantly found in SSc patients than controls, predominantly among females (p= 0.009) with longer disease duration (p= 0.03) and sever skin involvement (p= 0.0001). Vitamin D was correlated with SSc severity scale as well as thinner femoral cartilage sites studied by MSU, while some sites shown correlation with disease activity parameters.